Bioinformatics analysis and experimental validation of the potential relationship between bacterial lipopolysaccharide and oral squamous cell carcinoma - Wannan Gao; Hongyan Yuan; Song Qing (PLoS ONE, 2025)
Background Advances in science and medicine have led to the identification of bacterial virulence factors (including lipopolysaccharide, LPS) and their key role in the occurrence and outcome of tumors. However, the effect of LPS on oral squamous cell carcinoma (OSCC) has yet to be fully understood. Objective Hence, based on host genes related to bacterial LPS, the study investigated the potential role and mechanism of oral bacteria in OSCC via bioinformatics analysis and experimental validation. Methods The sequencing datasets of OSCC were screened using the GEO database and the bacterial LPS-related genes were searched in the GeneCards database to identify the LPS-related differentially expressed genes (LR-DEGs) in OSCC. The molecular mechanism of bacteria affecting OSCC was explored through GO and KEGG enrichment analysis, as well as protein-protein interaction (PPI) network and module analysis. Subsequently, seven algorithms were integrated to identify the LPS-related hub genes (LRHGs), and their diagnostic specificities were explored by receiver operating characteristic (ROC) and transcription levels were verified by qRT-PCR. Immune infiltration was then analyzed. Results We found a total of 345 LR-DEGs. GO and KEGG enrichment analysis demonstrated that the LR-DEGs were mainly enriched in inflammation-related pathways including cytokine-cytokine receptor interaction and IL-17 signaling, suggesting that bacteria may promote the development of OSCC through LPS-related gene-mediated inflammatory response. PPI and module analysis results revealed the presence of a complex regulatory network involving LR-DEGs. Totally, five LRHGs (including Cxcl8, Cxcl10, Il-1β, Il-6 and Mmp9) were screened out. Based on ROC analysis, the five LRHGs represented potential diagnostic biomarkers for OSCC (AUC > 0.7). The results of qRT-PCR, WB, ELISA and IF indicated that all LRHGs were upregulated in OSCC (P < 0.05). Immune infiltration analysis showed that LRHGs were closely related to the immunocyte infiltration level, suggesting a potential target for OSCC immunotherapy. In this study, 345 LR-DEGs and 5 LRHGs were identified in bacterial LPS-regulated OSCC progression. Importantly, the 5 LRHGs may mediate the OSCC progression in the host through inflammation-related pathways. These findings suggest that bacterial LPS plays a vital role in OSCC. Conclusion Our study provides novel insights into the pathogenesis and development of oral bacteria in OSCC. The LRHGs identified in this study are crucial for the diagnosis of OSCC, and also provide new insights into the molecular mechanisms and targeted therapies of OSCC.